Analysis of Turkey's electric power demand forecast and generation models scenarios for the next ten years - (:unkn) unknown (World Scientific and Engineering Academy and Society, 2010)
The Turkish Government makes great efforts to increase the new and renewable energy resources, use new systems with low carbon emission instead of high carbon emission technologies, make energy saving and decrease the emission of Carbon-dioxide (CO2) and other sera gases by increasing the energy productivity by means of preventing losses in energy distribution systems. In production of electric energy, the high rate of the imported fossil fuel is a significant advantage. With this regard, the investments made to local and especially renewable energy resources must be increased. In this study, the technical and economical parameters such as primary energy resources, demand increases and price fluctuations are examined in detail. In the study legal regulations made for that purpose are also considered. By using the data published by Turkish Electricity Transmission Company (TEIAS), analysis of important parameters such as energy demand increase rates, investment plans, change in emission rates expected to occur until year of 2020 according to two scenarios, in terms of sustainability in energy production, is made. Consequently, within following ten years, a very small development in energy investment policies of Turkey is expected with effect of legal arrangements in favor of renewable energy resources. However, this increase is very low according to the potential usable in the country. This situation decreases the competition power of country with the OECD countries in terms of energy prices. For a sustainable development, the country must make significant changes in the foreigndependent energy production policies. In the policies to be determined, supplying of continuously increasing demand from local resources must be encouraged. In some regions of the country, measures to decrease the air pollution that causes important social reactions and health problems must be taken and by rapidly completing the privatization studies, the weight of private sector also on installation of new plants must be increased.
Keywords: Energy price; Geothermal energy resources; Greenhouse gases; Investment plan; Legal arrangements; Solar; Sustainable consumption; Turkey; Wind